Investigation of structural and optical properties of CdO nanoparticles via peel of Citrus x sinensis. (2021) - Fall, Adama; Sackey, Juliet; Mayedwa, Noluthando; Ngom, Balla Diop
Abstract: The present work reports on the bio-synthesis and characterization of cadmium oxide nanoparticles (CdO) which were prepared via green synthesis method validating for the first time that oranges peel skin (Citrus x Sinensis) extract is an effective bio-oxidizing/bio-reducing /chelating agent. The prepared nanoparticles were characterized by various techniques such as X-rays diffraction, attenuated total reflection-Fourier transform infrared, Photoluminescence as well as diffuse reflectance. Synthesized samples annealed at various temperature of 200 °C, 300 °C, 400 °C reveal Bragg peaks which were matched to fcc structure of Monteponite CdO while ATR analysis show absorption bands at 548 and 617 cm −1 characteristic of CdO. Photoluminescence spectroscopy analysis shows emission peaks centered at 520 nm meanwhile diffuse reflectance measurement recorded reflectance of 60%, 15%, 8% for samples annealed at 400 °C, 300 °C, 200 °C with respective bandgap of 2.19 eV, 2.42 eV, 2.45 eV.